1995
DOI: 10.1111/j.1464-5491.1995.tb00466.x
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Hepatitis C Infection in Afro‐Caribbean Patients with Type 2 Diabetes and Abnormal Liver Function Tests

Abstract: Moderate elevations of serum transaminases are frequently found in patients with diabetes mellitus and are often attributed to fatty infiltration of the liver without further investigation. Recent studies of patients with end-stage liver disease have suggested a possible association between Hepatitis C virus (HCV) antibody positivity and the development of diabetes (mostly Type 2). As a first step in the examination of any potential association between HCV and Type 2 diabetes in subjects without overt liver di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(82 citation statements)
references
References 19 publications
8
70
0
4
Order By: Relevance
“…The present study showed that the overall prevalence of HCV antibodies in type 2 diabetic patient at Sharkia governorate is 38.7 % which is much higher than that reported by The Egypt Demographic and Health Survey (2008 EDHS), which stated that the prevalence of HCV in general population is 14.7% among a nationally representative sample of 11,126 Egyptians aged 15-59 years old. The higher prevalence of HCV antibodies in type 2 diabetic patients than general population is in agreement with previous studies that have noted a 2-to 10-fold increase in the sero-prevalence of HCV infection in diabetic patients (15) (16) . Also in a study conducted in 2004, Custro et al (17) stated that, about 42.3% of the patients with impaired glucose tolerance were infected with HCV.…”
Section: Hepatitis C Virus (Hcv) Infection Is a Major Public Health Csupporting
confidence: 81%
“…The present study showed that the overall prevalence of HCV antibodies in type 2 diabetic patient at Sharkia governorate is 38.7 % which is much higher than that reported by The Egypt Demographic and Health Survey (2008 EDHS), which stated that the prevalence of HCV in general population is 14.7% among a nationally representative sample of 11,126 Egyptians aged 15-59 years old. The higher prevalence of HCV antibodies in type 2 diabetic patients than general population is in agreement with previous studies that have noted a 2-to 10-fold increase in the sero-prevalence of HCV infection in diabetic patients (15) (16) . Also in a study conducted in 2004, Custro et al (17) stated that, about 42.3% of the patients with impaired glucose tolerance were infected with HCV.…”
Section: Hepatitis C Virus (Hcv) Infection Is a Major Public Health Csupporting
confidence: 81%
“…Prevalência de infecção pelo vírus da hepatite C em pacientes com diabetes melito tipo 2 até 28%, sendo que os maiores índices são encontrados quando se analisam particularmente os diabéticos com elevação das aminotransferases (5,14,17,18,19) . Neste estudo os pacientes com DM tipo 2 apresentaram taxas mais elevadas de ALT que os diabéticos tipo 1 (P <0,01).…”
Section: Discussionunclassified
“…Mais recentemente, estudos epidemiológicos sugerem que o diabetes melito (DM) possa representar também manifestação da infecção crônica pelo VHC (12,13) . Vários autores relataram prevalência aumentada de infecção pelo VHC em diabéticos tipo 2, em contraste com a população geral (5,15,18,19) . A possível associação entre VHC e DM também é sugerida por estudos transversais que encontraram prevalência aumentada de DM tipo 2 em pacientes com hepatite crônica C, quando comparada à observada em pacientes com outras formas de doença hepática crônica, mesmo na ausência de cirrose (1,2,6,9,11,13) .…”
Section: Introductionunclassified
“…Asymptomatic, moderate serum aminotransferase elevation has frequently been found in patients with DM, particularly in those with T2DM [24,25] . This phenomenon has often been related to fatty infiltration of the liver without further investigation [26,27] . In particular, steatosis has been related to IR and T2DM, beyond intracellular fat accumulation [28] .…”
Section: Development Of T2dmmentioning
confidence: 99%